Site-Specific Radioiodination of an Anti-HER2 Single Domain Antibody Fragment with a Residualizing Prosthetic Agent - Feng, Yutian (Nucl Med Biol, 2020)
INTRODUCTION: As a consequence of their small size, high stability and high affinity, single domain antibody fragments (sdAb) are appealing targeting vectors for radiopharmaceutical development. With sdAbs binding to internalizing receptors like HER2, residualizing prosthetic agents can enhance tumor retention of radioiodine, which until now has been done with random labeling approaches. Herein we evaluate a site-specific strategy utilizing a radioiodinated, residualizing maleimido moiety and the anti-HER2 sdAb 5F7 bearing a GGC tail for conjugation. METHODS: Maleimidoethyl 3-(guanidinomethyl)-5-iodobenzoate ([(131)I]MEGMB) and its N-succinimidyl ester analogue, iso-[(125)I]SGMIB, were labeled by halodestannylation and conjugated with 5F7GGC and 5F7, respectively. Radiochemical purity, immunoreactivity and binding affinity were determined. Paired-label experiments directly compared iso-[(125)I]SGMIB-5F7 and [(131)I]MEGMIB-5F7GGC with regard to internalization/residualization and affinity on HER2-expressing SKOV-3 ovarian carcinoma cells as well as biodistribution and metabolite distribution in athymic mice with subcutaneous SKOV-3 xenografts. RESULTS: [(131)I]MEGMIB-5F7GGC had an immunoreactivity of 81.3% and K(d) = 0.94 ± 0.27 nM. Internalization assays demonstrated high intracellular trapping for both conjugates, For example, at 1 h, intracellular retention was 50.30 ± 3.36% for [(131)I]MEGMIB-5F7GGC and 55.95 ± 3.27% for iso-[(125)I]SGMIB-5F7, while higher retention was seen for iso-[(125)I]SGMIB-5F7 at later time points. Peak tumor uptake was similar for both conjugates (8.35 ± 2.66% ID/g and 8.43 ± 2.84% ID/g for iso-[(125)I]SGMIB-5F7 and [(131)I]MEGMIB-5F7GGC at 1 h, respectively); however, more rapid normal tissue clearance was seen for [(131)I]MEGMIB-5F7GGC, with a 2-fold higher tumor-to-kidney ratio and a 3-fold higher tumor-to liver ratio compared with co-injected iso-[(125)I]SGMIB-5F7. Consisted with this, generation of labeled catabolites in the kidneys was higher for [(131)I]MEGMIB-5F7GGC. CONCLUSION: [(131)I]MEGMIB-5F7GGC offers similar tumor targeting as iso-[(125)I]SGMIB-5F7 but with generally lower normal tissue uptake. ADVANCES IN KNOWLEDGE AND IMPLICATION FOR PATIENT CARE: The site specific nature of the [(131)I]MEGMIB reagent may facilitate clinical translation, particularly for sdAb with compromised affinity after random labeling.